Changes in the chemical profile of cephalic salivary glands of Scaptotrigona postica (Hymenoptera, Meliponini) workers are phase related - Poiani, Silvana B. [UNESP]; Morgan, E. David; Drijfhout, Falko P.; Da Cruz-Landim, Carminda [UNESP] (The Company of Biologists, 2015)
Most advanced eusocial bees recruit their nest mates to food resources. Recent studies in Meliponini species have revealed that the cephalic salivary (labial) glands (CSGs) are responsible for the production of scent trail pheromones. Studies on CSGs have shown that changes occur in worker glandular cell morphology from emergence from brood combs until forager phase, which may be correlated to changes in the composition of the CSG secretion. However, the composition of the CSG secretion and the chemical changes that occur in it according to the worker's life phase or tasks performed are unknown for many species, including Scaptotrigona postica. In this study, the chemical profile of CSG secretion in S. postica workers was studied. Glands were taken from specimens that were newly emerged (NE), working in the brood comb area (CA) and foraging (FO), and were analyzed by gas chromatography-mass spectrometry. The results showed that the glandular secretion consists of oxygenated compounds of middle volatility (acids, alcohols, aldehydes, ketones, esters and ether), and their quantity varies among the different life phases, increasing as the individual moves fromintra- to extra-colonial activities. The NE phase contained the smallest variety and quantity of compounds. Because of the variability of compounds, the CA workers were separated into three subgroups according to the chemical constitution of their secretion. Forager workers showed the largest quantity and variety of chemical compounds. The major compounds in forager gland secretion were 7-hexadecen-1-yl acetate and 5-tetradecen-1-yl acetate. Statistical analysis indicates that the chemical composition of glandular secretion is phase related.
Keywords: Ester; GC-MS; Labial glands; Life phases; Multivariate statistics; Stingless bee